The association among SES, screen time, and outdoor play in children at different ages: The GECKO Drenthe study - Lu, Congchao; Wiersma, Rikstje; Corpeleijn, Eva (Frontiers in Public Health, 2023)
Introduction: This study examined the association between socioeconomic status (SES), screen time, and outdoor play in children at different ages in the GECKO Drenthe birth cohort study. Methods: Valid data were obtained from two surveys at age 3-4 years and age 10-11 years. Screen time (TV watching and computer use) and outdoor play were reported by parents. Childhood SES was derived by a synthetic ‘Equivalized Household Income Indicator’, an estimated disposable income. Quantile regression models (cross-sectional analysis) and linear regression models (change between 3-4 and 10-11 years) were used. Results: In general, screen time increased strongly from a median of 51 min/day at 3-4 years (n = 888) to 122 min/day at 10-11 years (n = 1023), whereas time spent on outdoor play remained stable over age (77 min/day at 3-4 years, 81 min/day at 10-11 years). More time spent on outdoor play (50th quantile) was found in children with low SES families at 3-4 years, while, at 10-11 years, more outdoor play was found in the high SES group. At 10-11 years, in the higher ranges of screen time, children from high SES had relatively lower screen time (50th quantile: −10.7 (−20.8; −0.6); 75th quantile: −13.6 (−24.4; −2.8). In the longitudinal analysis (n = 536), high SES was associated with an increasing time spent on outdoor play (11.7 (2.7; 20.8)). Conclusions: Socioeconomic disparities in children’s outdoor play and screen behaviour may be more obvious with increasing age. Low SES may facilitate both outdoor play (at 3-4 years) and screen time (at 10-11 years), however, children from high SES families develop slightly more favourable behaviour patterns with age.